2018
DOI: 10.1111/ajt.14726
|View full text |Cite
|
Sign up to set email alerts
|

Changing demographics of heart donors: The impact of donor drug intoxication on posttransplant survival

Abstract: Recent reports have shown an increase in the number of organ donors from drug intoxication. The impact of donor drug use on survival after cardiac transplant remains unclear. The aim of our study was to illustrate changes in donor death mechanisms and assess the impact on posttransplant survival. We queried United Network of Organ Sharing thoracic transplant and deceased donor databases to identify patients undergoing heart transplantation between 2005 and 2015. We evaluated annual trends in donor death mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Neither of these studies was able to differentiate from opioid and nonopioid causes of death, though based on the US national statistics above, the majority of cases will involve opioids alone (prescription or illicit) or often in combination with other drugs. Other reports dealing separately with hearts and lungs have also recently shown no adverse effects on survival . Thus, heart and lung donors from drug overdose patients should be considered for transplantation.…”
Section: Cardiothoracic Transplantation Outcomes With Opioidsmentioning
confidence: 97%
“…Neither of these studies was able to differentiate from opioid and nonopioid causes of death, though based on the US national statistics above, the majority of cases will involve opioids alone (prescription or illicit) or often in combination with other drugs. Other reports dealing separately with hearts and lungs have also recently shown no adverse effects on survival . Thus, heart and lung donors from drug overdose patients should be considered for transplantation.…”
Section: Cardiothoracic Transplantation Outcomes With Opioidsmentioning
confidence: 97%
“…Recent studies have looked at the UNOS cause of death field and have found that drug intoxication donor cause of death is not associated with adverse post-transplant outcomes. 10 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, posttransplant survival of opioid-intoxicated donor hearts and lungs is similar to that from nonintoxicated donors. 11,12 Even when dealing with brain-dead donors after ingestion of toxic substances mainly metabolized by the liver as, for instance, ethylene glycol or brodifacoum, a rodenticide with a potent anticoagulant effect, good graft outcome and acceptable recipient survival have been reported in the literature. Liver biopsy, hemodialysis to accelerate toxic clearance, and verification of the absence of the toxic substance in blood samples are the suggested strategies to optimize results.…”
Section: Discussionmentioning
confidence: 99%